1978
DOI: 10.1136/bmj.1.6113.610
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of vincristine-induced neuropathy in lymphomas.

Abstract: and conclusions The incidence of vincristine-induced neuropathy was studied in 60 unselected patients, of whom 23 had lymphoma and 37 had other malignant disease. All were treated with vincristine combined with other cytotoxic agents. Fourteen of the patients with lymphoma (61%) developed neuropathy compared with five patients with leukaemia or non-lymphoid cancer (14%), even though all patients received comparable doses of vincristine. The difference between the two groups in the incidence of neuropathy was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Furthermore, several studies report advanced age in pediatric patients as a clinical risk factor [61, 69, 73]. However, some studies do not find this correlation in pediatric or adult patients [44, 49] and others even suggest the opposite for both groups [54, 88, 95].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies report advanced age in pediatric patients as a clinical risk factor [61, 69, 73]. However, some studies do not find this correlation in pediatric or adult patients [44, 49] and others even suggest the opposite for both groups [54, 88, 95].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that neuropathy incidence could be disease dependent given that a significantly higher incidence in patients suffering from lymphoma is observed compared with nonlymphoid cancer patients (e.g., leukemia, breast cancer, malignant melanoma) [88]. Fourteen out of 23 patients with lymphoma and 5/37 patients without lymphoma developed neuropathy despite comparable dosage [88], and concordant observations were made by others [46]. A higher percentage of lymphoma patients have elevated levels of serum alkaline phosphatase, which significantly prolongs elimination of vincristine and results in longer vincristine exposure and associated toxicities [46].…”
Section: Resultsmentioning
confidence: 99%
“…However, in Watkins' series, the rate of neuropathy was lower. In this study on adult patients with lymphoma treated with vincristine (0.14 mg/kg), neuropathy was detected in 61% of the cases [10]. One of probable causes of difference in reports about neuropathy is that the prevalence and severity is individualspecific.…”
Section: Discussionmentioning
confidence: 69%
“…These findings may arise from autonomic damage to the colon. Toxic effects are dose related and can be influenced by advancing age, concomitant liver damage, and type of malignancy [4].…”
Section: Discussionmentioning
confidence: 99%